Low dose insulin infusion versus the standard dose in children with diabetic ketoacidosis: a meta-analysis - Mohamed Mohamed Belal; Basma Badrawy Khalefa; Eslam Mohammed Rabea; Mazen Negmeldin Aly Yassin; Mohamed Nabih Bashir; Malak Mohamed Abd El-Hameed; Omar Elkoumi; Saad Mohamed Saad; Loubna Mohamed Saad; Mohamed Hamouda Elkasaby (Future Science OA)
Aim: This systematic review aims to consolidate findings from current clinical trials that compare the effectiveness of insulin infusion at 0.05 IU/kg/h versus 0.1 IU/kg/h in managing pediatric diabetic ketoacidosis. Methods: We searched several databases, including PubMed, Embase, Scopus, Cochrane Central and Web of Science. Our primary outcomes were time to reach blood glucose ≤250 mg/dl and time to resolution of acidosis. Secondary outcomes included rate of blood glucose decrease per hour, incidence of hypoglycemia, hypokalemia, treatment failure, and cerebral edema. Results & conclusion: The present study establishes that a low insulin dose exhibits comparable efficacy to the standard dosage for managing pediatric patients suffering from diabetic ketoacidosis, with a lower incidence of complications.